Valorizing the organic fraction of municipal solid waste by producing black soldier fly larvae and biomethane in a biorefinery approach. (15th December 2022) - Papa, Gabriella; Scaglia, Barbara; D'Imporzano, Giuliana; Savoldelli, Sara; Jucker, Costanza; Colombini, Stefania; Toschi, Ivan; Adani, Fabrizio
Abstract: The use of organic fraction municipal solid waste (OFMSW) was evaluated by rearing black soldier fly larvae (BSFL) and by producing biomethane from the derived residual larval waste (R-OFMSW). To do so, OFMSW was sampled from two full scale plants during the year (four seasons) and OFMSW textures were also studied by considering untreated and pulped waste. Residual larval waste was then used to produce biomethane, closing the biorefinery process, and complete mass and energy balances are provided. On average, the larvae production was 155 ± 58 ( n  = 16) g kg − 1 OFMSWDM and biogas from R-OFMSW was 138 NL kg − 1 OFMSWDM ( n  = 16). No differences were observed considering seasonality, waste plants and OFMSW texture. Energy balance indicated that 37% of OFMSW energy content (ECOFMSW ) was recovered as the sum of BSFL and biomethane from R-OFMSW, which was much lower than the energy recovered by producing solely biomethane directly from OFMSW, i.e. 50% of ECOFMSW, because BSFL consumed a large part of the potential of OFMSW. Graphical abstract: Image 1 Highlights: A biorefinery approach valorizing organic fraction of wastes (OFMSW) was proposed. OFMSW was used rearing black soldier fly larvae (BSFL). Residual waste was then used to produce biomethane closing the loop. Energy balance indicated that 37% of OFMSW energy content was recovered. The whole biorefinery gave negative revenue.